Comparing depth-dependent curing radiant exposure and time of curing of regular and flow bulk-fill composites - Jose Augusto RODRIGUES; Ilana Pais TENORIO; Ginger Baranhuk Rabello de MELLO; André Figueiredo REIS; Chiayi SHEN; Jean-François ROULET (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The effect of restoration depth on the curing time of a conventional and two bulk-fill composite resins by measuring microhardness and the respective radiosity of the bottom surface of the specimen was investigated. 1-, 3- and 5-mm thick washers were filled with Surefil SDR Flow-U (SDR), Tetric EvoCeram Bulk Fill-IVA (TEC) or Esthet-X HD-B1 (EHD), and cured with Bluephase® G2 for 40s. Additional 1-mm washers were filled with SDR, TEC or EHD, placed above the light sensor of MARC®, stacked with pre-cured 1-, 3- or 5-mm washer of respective material, and cured for 2.5~60s to mimic 2-, 4- and 6-mm thick composite curing. The sensor measured the radiosity (EB) at the bottom of specimen stacks. Vickers hardness (VH) was measured immediately at 5 locations with triplicate specimens. Nonlinear regression of VH vs EB by VH=α[1-exp(-EB/β)] with all thickness shows that the values of α, maximum hardness, are 21.6±1.0 kg/mm2 for SDR, 38.3±0.6 kg/mm2 for TEC and 45.3±2.6 kg/mm2 for EHD, and the values of β, rate parameter, are 0.40±0.06 J/cm2 for SDR, 0.77±0.04 J/cm2 for TEC and 0.58±0.09 J/cm2 for EHD. The radiosity of the bottom surface was calculated when the bottom surface of each material attained 80% of α of each material. The curing times for each material are in agreement with manufacturer recommendation for thickness. It is possible to estimate time needed to cure composite resin of known depth adequately by the radiosity and microhardness of the bottom surface.